Snakes, Ladders, and Learning? Rethinking Critical Thinking in Geography through QR-Gamified Case Pedagogy - Umi Nurlaila Aulia (Future Space: Studies in Geo-Education, 2025)
The importance of critical thinking skills that students have requires an appropriate learning model. The aim of this research is to determine the effect of the Case Based Learning (CBL) model assisted by QR code Snakes and Ladders media on students' critical thinking abilities in the geography subject. This research used a quasi-experimental method with a posttest-only design. Two classes, which were confirmed to be equivalent based on previous average scores (67.77 and 68.74), were randomly assigned as the experimental and control groups. The independent variable (X) is the CBL model assisted by the QR code Snakes and Ladders, and the dependent variable (Y) is students' critical thinking, which was measured using posttest sheets. The CBL model assisted by the QR code Snakes and Ladders was found to have a significant influence on critical thinking skills, as evidenced by the Independent Sample T-Test significance value of 0.043 < 0.05, which means H1 is accepted and H0 is rejected. The results showed the experimental class average (73.06) was higher than the control class (63.43). Research findings indicate: 1) The CBL model with the media has a significant effect on critical thinking skills; 2) The case analysis syntax has the most influence; and 3) The 'analysis' indicator of critical thinking is the most significant in both classes.